Flexible water excitation for fat‐free MRI at 3T using lipid insensitive binomial off‐resonant RF excitation (LIBRE) pulses. Issue 6 (20th November 2017) - Bastiaansen, Jessica A.M.; Stuber, Matthias
Abstract : Purpose: To develop a robust and flexible low power water excitation pulse that enables effective fat suppression at high magnetic field strength. Methods: A water excitation method that uses spatially non‐selective pulses was optimized in numerical simulations, and implemented and tested in phantoms and healthy volunteers at 3T. The lipid insensitive binomial off‐resonant excitation (LIBRE) pulse comprises two low power rectangular subpulses that have a variable frequency offset, phase offset and duration. The capability and extent of LIBRE fat suppression was quantitatively compared with conventional fat saturation (FS) and water excitation (WE) techniques. Results: LIBRE enables simultaneous water excitation and near complete fat suppression in large volumes at 3T as demonstrated by numerical simulations, and experiments. In phantoms and in human subjects, the frequency responses matched well with those from the numerical simulation. Comparing FS and WE, LIBRE demonstrated an improved robustness to magnetic field inhomogeneities, and a much more effectively suppressed fat signal. This applied for a range of pulse durations and pulses as short as 1.4 ms. Conclusion: A flexible water excitation method was developed that shows robust, near complete fat suppression at 3T. Magn Reson Med 79:3007–3017, 2018. © 2017 International Society for Magnetic Resonance in Medicine.